2016
DOI: 10.1124/jpet.116.235838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketamine and Ketamine Metabolites on Evoked Striatal Dopamine Release, Dopamine Receptors, and Monoamine Transporters

Abstract: Following administration at subanesthetic doses, (R,S)-ketamine (ketamine) induces rapid and robust relief from symptoms of depression in treatment-refractory depressed patients. Previous studies suggest that ketamine's antidepressant properties involve enhancement of dopamine (DA) neurotransmission. Ketamine is rapidly metabolized to (2S,6S)-and (2R,6R)-hydroxynorketamine (HNK), which have antidepressant actions independent of Nmethyl-D-aspartate glutamate receptor inhibition. These antidepressant actions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 76 publications
9
81
2
Order By: Relevance
“…Indeed, a net result of all these processes is a sustained potentiation of excitatory synapses in cortico-mesolimbic brain circuits involved in the maintenance of mood and stress-reactivity 190 . Additional mechanisms, not discussed in the present review, include ketamine’s effects on the monoaminergic systems 191194 , as well as its anti-inflammatory actions, which are postulated to be involved in the mechanisms underlying its antidepressant actions; the reader is directed to reviews by Sleigh et al (2014) 195 and Loix et al (2011) 196 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a net result of all these processes is a sustained potentiation of excitatory synapses in cortico-mesolimbic brain circuits involved in the maintenance of mood and stress-reactivity 190 . Additional mechanisms, not discussed in the present review, include ketamine’s effects on the monoaminergic systems 191194 , as well as its anti-inflammatory actions, which are postulated to be involved in the mechanisms underlying its antidepressant actions; the reader is directed to reviews by Sleigh et al (2014) 195 and Loix et al (2011) 196 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it was recently demonstrated that higher brain levels of the ( 2S,6S;2R,6R )-HNK metabolite of ketamine in female mice might be associated with these enhanced antidepressant behavioral actions of ketamine in female compared to male mice [45]. ( 2S,6S;2R,6R )-HNK is the most prominent HNK metabolite present in the plasma and brain of mice [45, 102] and the plasma of treatment-resistant patients with depression [103] following a single ketamine administration. Similar to the preclinical findings, higher levels of this metabolite have been measured in the plasma of female patients compared with male patients following a single infusion of ketamine, but this difference was not associated with any significantly different antidepressant responses in these patients [103].…”
Section: Mechanisms Underlying Fast/rapid Onset Antidepressants Acmentioning
confidence: 99%
“…Indeed, ketamine and its metabolites, in particular (2R,6R)-HNK, are still present in plasma and brain 30-60 min after their injection. 29 We did not examine the effect of chronic administration of ketamine or (2R,6R)-HNK, because antidepressant actions are observed following a single injection and chronic ketamine treatment has no effect on depression-like behavior. 30 We measured fEPSP/PSs mediated by AMPARs in the core region of the NAc in brain slices as described previously 28 ( Supplementary Figure 1).…”
Section: Ketamine Induces Lasting Impairment Of Ltp In the Nacmentioning
confidence: 99%